Unraveling Dengue Dynamics: In-Depth Epidemiological and Entomological Analyses in Bengaluru, India - Vani H. C.; Sujit Nath N.; Jaiswal M. K.; Tiwari R. P.; Bharathi P.; Asmita B.; Shankar G.; Jithen C.; Pallavi V. D.; Srinivas V.; Ashok M.; Mahamood Shariff; et al. (Journal of Tropical Medicine)
In view of the increased number of detected dengue cases in Bengaluru, a request for situation analysis was received from local health authorities in the selected area. The study included epidemiological and entomological assessments to understand the same. The immature forms collected were allowed to emerge, pooled, and processed for vector incrimination. In the surveyed population (347), 20 (5.8%) reported fever cases and 12 (3.5%) were confirmed as dengue cases among the 102 families. Stegomyia indices were high. Vector incrimination studies revealed pools positive for the presence of dengue virus in flower pots, fridge trays, plastic barrels, and rubber tires habitats. This study highlights the increased risk of dengue fever incidence in communities wherepoor intra and peri-domestic sanitation practices are prevailing and recommendsregular entomological surveillance of denguevirus in its vector population..